Sistem Informasi Pelayanan Kesehatan Berbasis Web Di Puskesmas Sambi Dengan Laravel - Dwiki Reza Nova Alvianto; Ihsan Cahyo Utomo (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Sambi Health Center is one of the first-level health care facilities that has an important role in providing basic medical services to the community. However, in its implementation, the service process is still carried out manually, especially in recording patient data, managing queues, and delivering information. This has an impact on low efficiency, potential data input errors, and delays in service. To answer these problems, this study developed a web-based health service information system using the Laravel framework. The system is designed to automate the service process, minimize errors, and speed up the workflow. The Model-View-Controller (MVC) architecture is used to separate logic and interface, making the system easier to develop and maintain. The test results using the blackbox method and System Usability Scale (SUS) obtained a score of 90.4 with the category